Annual Report 1998-99 - Planning Commission (Planning Commission, 1998)
The year 1998-99 marks the second year of the Ninth Five Year Plan (1997-2002). The Approach paper to the Ninth Five Year Plan envisaged a base line growth scenario of 6.2 per cent per annum on the average for the Ninth Plan period. It was also indicated that an accelerated growth scenario of 7 per cent per annum was feasible provided certain policy decisions were adopted by the Centre and the States.
Government of India Planning Commission
Government of India Planning Commission